Studi Kasus Kemampuan Komunikasi Interpersonal Siswa MAN 2 Kota Semarang - Fitri Wihardini; Siti Fitriani; Tsalitsia Urfy Maretha (Jurnal Pendidikan dan Konseling (JPDK), 2023)
The purpose of this study was to determine the interpersonal communication skills of students at MAN 2 Semarang City. This research was conducted because now many children do not have good interpersonal skills. This type of research uses the case study method. Data collection techniques using observation, interviews. The research methodology used is qualitative research. The samples taken from this were students of MAN 2 Semarang City who were taken through a random sampling technique. From this study it shows that students of MAN 2 Semarang City have good interpersonal communication skills and can speak politely. Therefore interpersonal communication in children is one of the things that must be of concern to parents. Keywords: Communication Skills, Interpersonal Communication